Inflammation as a Predictor of Abdominal Aortic Aneurysm Growth and Rupture: A Systematic Review of Imaging Biomarkers. Issue 3 (September 2016) - Jalalzadeh, H.; Indrakusuma, R.; Planken, R.N.; Legemate, D.A.; Koelemay, M.J.W.; Balm, R.
Abstract : Background: Methods are required to identify abdominal aortic aneurysms (AAAs) at increased risk of rupture. Inflammatory characteristics of AAA can be visualised using advanced imaging techniques and have been proposed as potential predictors of aneurysm progression. The objective of this review was to determine which inflammatory imaging biomarkers are associated with AAA growth and rupture. Methods: A systematic review was carried out in accordance with the PRISMA guidelines. The electronic databases of Medline (PubMed), Embase, and the Cochrane Library were searched up to January 1, 2016 for studies to determine the potential association between inflammatory imaging biomarkers and AAA growth or rupture. Results: Seven studies were included, comprising 202 AAA patients. 18 F-fluoro-deoxy-glucose positron emission tomography ( 18 F-FDG PET-CT) was evaluated in six studies. Magnetic resonance imaging with ultrasmall superparamagnetic particles of iron oxide (USPIO-MRI) was evaluated in one study. Two of six 18 F-FDG PET-CT studies reported a significant negative correlation ( r = .383, p = .015) or a significant negative association ( p = .04). Four of six 18 F-FDG PET-CT studies reported no significant association between 18 F-FDG uptake and AAA growth. The single study investigating USPIO-MRI demonstrated that AAA growth was three times higher in patients with focal USPIO uptake in the AAA wall compared to patients with diffuse or no USPIO uptake in the wall (0.66 vs. 0.24 vs. 0.22 cm/y, p = .020). In the single study relating 18 F-FDG uptake results to AAA rupture, the association was not significant. Conclusions: Current evidence shows contradictory associations between 18 F-FDG uptake and AAA growth. Data on the association with rupture are insufficient. Based on the currently available evidence, neither 18 F-FDG PET-CT nor USPIO-MRI can be implemented as growth or rupture prediction tools in daily practice. The heterogeneous results reflect the complex and partially unclear relationship between inflammatory processes and AAA progression.